Accountability Practices Based on Zakat Institutions Website in Indonesia - Wahyudi, Muhamad; Herianingrum, Sri; Ratnasari, Ririn Tri (Jurnal Riset Akuntansi dan Keuangan, 2021)
Website-based accountability is the right choice for zakat institutions to increase the positive image of the public. This study aims to reveal how zakat institutions use the website in disclosing public accountability. This research is a qualitative research with a content analysis technique approach to test how big the accountability index is based on the zakat institution website. The research sample consisted of 26 zakat institutions at the national level in Indonesia. Inter-rater analysis techniques are used to test data reliability. The results reveal that the practice of website-based accountability in zakat institutions in Indonesia is still low. This can be seen from the three-dimensional score, namely 43% transparency, 34% accountability, and 27% responsibility and the total score on the average website-based accountability index only gets a score of 299 out of 637 or 43%. The implication of this research is that the use of websites as a means of delivering public accountability can increase public integrity and trust in zakat institutions.